Fear of Missing Out (FOMO) dengan Kecanduan Media Sosial pada Mahasiswa - Linda Kusuma Dewi Rahardjo; Christiana Hari Soetjiningsih (Kuras Institute, 2022)
This study is a quantitative study that aims to determine the relationship between Fear of Missing Out and social media addiction in college students. The participants in this study were 67 active students of the Satya Wacana Christian University Faculty of Psychology, class of 2018-2020 who used social media for a minimum of 5 hours. The research instrument uses 2 measuring instruments, namely the Bergen Social Media Addiction Scale (BMAS) Indonesian version modified by Maheswari and Dwiutami (2013) and the Indonesian Fear of missing Out Scale (FoMOS) modified by Kaloeti, Kurnia, and Tahamata (2021). Based on the results of data analysis using the Pearson product moment correlation test, there is a significant positive relationship between Fear of Missing Out and social media addiction with a correlation coefficient of 0.564 with a significance value of 0.000 (p < 0. 05) which means that the higher the level of Fear of Missing Out, the higher the level of addiction to social media, and conversely the lower the level of Fear of Missing Out, the lower the level of addiction to social media. The results of this study can be used as a basis for making activities to reduce the level of addiction to social media.